A novel method to measure sensory nerve conduction of the posterior antebrachial cutaneous nerve. Issue 2 (7th June 2022) - Hemmi, Shoji; Kurokawa, Katsumi; Nagai, Taiji; Asano, Akio; Murakami, Tatsufumi; Mihara, Masahito; Sunada, Yoshihide
Abstract: Introduction/Aims: Posterior antebrachial cutaneous (PABC) nerve conduction studies could be useful for distinguishing PABC neuropathy from C7 radiculopathy. In the conventional method using an antidromic method, the sensory nerve action potential (SNAP) is sometimes followed by a large volume‐conducted motor potential. In this report we describe a reliable nerve conduction study using an orthodromic method for recording SNAPs of the PABC nerve. Methods: Thirty‐six healthy volunteers participated in this study. PABC SNAPs were recorded by placing a surface‐active electrode 2 cm anterior to the lateral epicondyle. The PABC nerve was stimulated 10 cm distal to the active recording electrode along a line from the recording point to the mid‐dorsum of the wrist, midway between the radial and ulnar styloid processes. We also performed PABC nerve conduction studies using an antidromic method and compared the findings. Results: PABC SNAPs were recorded bilaterally from all subjects. The mean peak‐to‐peak amplitude for SNAPs was 13.4 ± 4.8 μV. Mean maximum conduction velocity was 62.7 ± 3.9 m/s and mean negative peak conduction velocity was 51.2 ± 2.6 m/s. The mean side‐to‐side difference in amplitude was 22.1 ± 16.0%. The mean amplitude of SNAPs obtained by our method was 48.9% higher than that of SNAPs obtained by the conventional method (13.4 vs 9.0 μV; P < .001). In contrast to the conventional method, our method enabled SNAPs to be recorded without a volume‐conducted motor potential. Discussion: The higher mean amplitude of SNAPs with our method enables them to be obtained easily.